mRNA lipid nanoparticles expressing cell-surface cleavage independent HIV Env trimers elicit autologous tier-2 neutralizing antibodies - Guenaga, Javier; Alirezaei, Mehrdad; Feng, Yu; Alameh, Mohamad-Gabriel; Lee, Wen-Hsin; Baboo, Sabyasachi; Cluff, Jocelyn; Wilson, Richard; Bale, Shridhar; Ozorowski, Gabriel; Lin, Paulo; Tam, Ying; et al. (Frontiers in Immunology, 2024)
The HIV-1 envelope glycoprotein (Env) is the sole neutralizing determinant on the surface of the virus. The Env gp120 and gp41 subunits mediate receptor binding and membrane fusion and are generated from the gp160 precursor by cellular furins. This cleavage event is required for viral entry. One approach to generate HIV-1 neutralizing antibodies following immunization is to express membranebound Env anchored on the cell-surface by genetic means using the natural HIV gp41 transmembrane (TM) spanning domain. To simplify the process of Env trimer membrane expression we sought to remove the need for Env precursor cleavage while maintaining native-like conformation following genetic expression. To accomplish these objectives, we selected our previously developed 'native flexibly linked' (NFL) stabilized soluble trimers that are both near-native in conformation and cleavage-independent. We genetically fused the NFL construct to the HIV TM domain by using a short linker or by restoring the native membrane external proximal region, absent in soluble trimers, to express the full HIV Env ectodomain on the plasma membrane. Both forms of cell-surface NFL trimers, without and with the MPER, displayed favorable antigenic profiles by flow cytometry when expressed from plasmid DNA or mRNA. These results were consistent with the presence of wellordered cell surface native-like trimeric Env, a necessary requirement to generate neutralizing antibodies by vaccination. Inoculation of rabbits with mRNA lipid nanoparticles (LNP) expressing membrane-bound stabilized HIV Env NFL trimers generated tier 2 neutralizing antibody serum titers in immunized animals. Multiple inoculations of mRNA LNPs generated similar neutralizing antibody titers compared to immunizations of matched NFL soluble proteins in adjuvant. Given the recent success of mRNA vaccines to prevent severe COVID, these are important developments for genetic expression of native-like HIV Env trimers in animals and potentially in humans.